2000
DOI: 10.1055/s-2000-6229
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a 9-Fluorenone Derived β-Amino Alcohol Ligand Depicting High Catalytic Activity and Pronounced Non-linear Stereochemical Effects

Abstract: The Jacobsen epoxidation of 9-alkylidenefluorenes 4a (ethylidene), 4b (benzylidene) and 4c (1-naphtylmethylene) with standard (R,R)-manganese salen catalyst has been studied. Both conversion and enantioselectivity depend on the steric bulk of the olefin substituent, best results being recorded with 4b (96% yield, 99% ee). The stereochemical course of the epoxidation of 4a is highly dependent on temperature and solvent, the ee of the resulting epoxide (S)-5a varying from 22% (-18°C, CH 2 Cl 2 ) to 49% (55°C, MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…76.5–78.0 °C (lit. 103–104 °C,9b 52–54 °C9d); 1 H NMR 300 MHz, CHCl 3 , 25°C, TMS): δ =7.90 (d, 3 J (H,H)=7 Hz, 1 H; H11), 7.88 (d, 3 J (H,H)=7 Hz, 1 H; H2), 7.71 (d, 3 J (H,H)=8 Hz, 1 H; H8), 7.66 (d, 3 J (H,H)=8 Hz, 1 H; H5), 7.28–7.46 (m, 4 H; H3, H4, H9, H10), 6.88 (q, 3 J (H,H)=8 Hz, 1 H; CCH), 2.42 (d, 3 J (H,H)=7.7 Hz, 3 H; CH 3 ); 13 C NMR (75 MHz, CDCl 3 , 25 °C, TMS): δ =130.4, 127.9, 127.3, 124.9, 124.5, 112.8, 112.7, 112.4, 112.3, 110.4, 109.6, 105.3, 104.9, 104.6, 38.9; MS (70 eV): m / z (%): 192 (100). 1 H NMR peak assignments are numbered according to Figure 2…”
Section: Methodsmentioning
confidence: 99%
“…76.5–78.0 °C (lit. 103–104 °C,9b 52–54 °C9d); 1 H NMR 300 MHz, CHCl 3 , 25°C, TMS): δ =7.90 (d, 3 J (H,H)=7 Hz, 1 H; H11), 7.88 (d, 3 J (H,H)=7 Hz, 1 H; H2), 7.71 (d, 3 J (H,H)=8 Hz, 1 H; H8), 7.66 (d, 3 J (H,H)=8 Hz, 1 H; H5), 7.28–7.46 (m, 4 H; H3, H4, H9, H10), 6.88 (q, 3 J (H,H)=8 Hz, 1 H; CCH), 2.42 (d, 3 J (H,H)=7.7 Hz, 3 H; CH 3 ); 13 C NMR (75 MHz, CDCl 3 , 25 °C, TMS): δ =130.4, 127.9, 127.3, 124.9, 124.5, 112.8, 112.7, 112.4, 112.3, 110.4, 109.6, 105.3, 104.9, 104.6, 38.9; MS (70 eV): m / z (%): 192 (100). 1 H NMR peak assignments are numbered according to Figure 2…”
Section: Methodsmentioning
confidence: 99%
“…Pericàs et al reported the highly enantioselective ethylation of aliphatic aldehydes in the presence of 6 mol% of their devised chiral N,O-ligand 36 ( Table 9) [39]. The reactions proceed smoothly in 4 h under the mild conditions and almost quantitatively give the Et-adducts in 90-98% ee.…”
Section: Enantioselective Diethylzinc Addition To Aliphatic Aldehydesmentioning
confidence: 97%
“…Specifically, selective azidation of diol (3a) gives an α-azido alcohol 12, and it could transform into α-amino alcohol via a facile hydrogenation. 63 Page 12 of 25 CCS Chemistry 13…”
Section: Synthetic Utilitymentioning
confidence: 99%